Analysis Of Acceptance Of E-Service Using Unified Theory Of Acceptance And Use Of Technology (Utaut) Faculty Of Engineering, Yogyakarta State University - Byan Dicky Novaldi (Institute of Computer Science (IOCS), 2020)
This study aims to determine the factors that influence the acceptance and use of the application of E-Service services at the Faculty of Engineering, Yogyakarta State University. The model used in this study is The Unified Theory of Acceptance and Use of Technology (UTAUT). This research method uses an explanative quantitative approach. The population in this study were students using E-Service at the Faculty of Engineering, Yogyakarta State University. Sampling of 100 students. The data collection method used is a questionnaire. The analysis technique uses Partial least square (PLS) analysis. The results of this study are that performance expectations have a positive effect on student interest in using E-Service, (Effort expectations have a positive effect on student interest in using E-Service.